Antihyperglycemic Effect of Ginkgo biloba Extract in Streptozotocin-Induced Diabetes in Rats. (20th December 2012) - Cheng, Daye; Liang, Bin; Li, Yunhui
Abstract : The Ginkgo biloba extract (GBE) has been reported to have a wide range of health benefits in traditional Chinese medicine. The aim of this study was to evaluate the antihyperglycemic effects of GBE on streptozotocin- (STZ-) induced diabetes in rats. Diabetes was induced in male Wistar rats by the administration of STZ (60 mg/kg b.w.) intraperitoneally. GBE (100, 200, and 300 mg/kg b.w.) was administered orally once a day for a period of 30 days. Body weight and blood glucose levels were determined in different experimental days. Serum lipid profile and antioxidant enzymes in hepatic and pancreatic tissue were measured at the end of the experimental period. Significant decreases in body weight and antioxidant ability and increases in blood glucose, lipid profile, and lipid peroxidation were observed in STZ-induced diabetic rats. The administration of GBE and glibenclamide daily for 30 days in STZ-induced diabetic rats reversed the above parameters significantly. GBE possesses antihyperglycemic, antioxidant, and antihyperlipidemia activities in STZ-induced chronic diabetic rats, which promisingly support the use of GBE as a food supplement or an adjunct treatment for diabetics.